Increasing data storage of coloured QR code using compress, multiplexing and multilayered technique - Azizi Abas; Yuhanis Yusof; Roshidi Din; Fazli Azali; Baharudin Osman (Institute of Advanced Engineering and Science, 2020)
Quick response (QR) code is a printed code of black and white squares that is able to store data without the use of any of the electronic devices. There are many existing researches on coloured QR code to increase the storage capacity but from time to time the storage capacity still need to be improved. This paper proposes the use ofcompress, multiplexing and multilayered techniques, as an integrated technique known as CoMM, to increase the storage of the existing QR code. The American Standard Code for Information Interchange (ASCII) text characters are used as an input and performance is measured by the number of characters that can be stored in a single black and white QR code version 40. The experiment metrics also include percentage of missing characters, number of produced QR code, and elapsed time to create the QR code. Simulation results indicate that the proposed algorithm stores 24 times more characters than the black and white QR code and 9 times more than other coloured QR code. Hence, this shows that the coloured QR code has the potential of becoming useful mini-data storage as it does not rely on internet connection.